Electron beam modulation by 3D printed plastic samples - Stuchebrov S. G. Sergey Gennadevich; Bulavskaya A. A. Angelina Aleksandrovna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna (2023, 2023)
Nowadays, modulation of the electron beam depth dose distributions in radiation therapy sessions is provided by sets of tissue equivalent plates or individually shaped thermoplastic boluses